Ansanus “the Baptizer” and the Problem of Siena’s Non-Existent Early Episcopacy (c. 1100–1600) - Anderson, Carol A. (Religions, 2025)
Medieval writers designated Siena as a “new city”. Seemingly confirming this assessment, the Sienese Church possessed no hagiographic tradition of early bishops that would prove that their urban settlement was a true civitas in late antiquity. As part of their effort to verify that their city had not only Roman but also early Christian origins, the Sienese, primarily spearheaded by lay officials, refashioned the image of their martyr-saint, Ansanus (d. 296). By the thirteenth century, the implication that the lay martyr had baptized the citizens was added to his second Latin passion narrative. Yet, only beginning in the fifteenth century do vernacular passions and images of Ansanus baptizing the Sienese appear, revealing that the baptismal event emerged as a defining point in the sacred history of the city and was communicated to citizens both textually and visually. These were produced at the behest of lay institutions, such as the Opera del Duomo and the communal government. By performing the sacrament of baptism, Ansanus fulfilled a crucial function of a proto-bishop, namely the transformation of the pagan Sienese into a true community of the baptized. Though some Sienese humanists sought to identify the earliest bishops, no episcopal cult was ever established. Considering that the default for other major cities in Italy was to identify and venerate their early bishops, Ansanus’s transformation into “the Baptizer” presents a case study of how saints could be adapted in unconventional ways to fix a problematic civic past.